Assessing vocational outcome expectancy in individuals with serious mental illness: a factor-analytic approach. (2nd January 2020) - Iwanaga, Kanako; Umucu, Emre; Wu, Jia-Rung; Yaghmaian, Rana; Lee, Hui-Ling; Fitzgerald, Sandra; Chan, Fong
Abstract: Background : Self-determination theory (SDT) and self-efficacy theory (SET) can be used to conceptualize self-determined motivation to engage in mental health and vocational rehabilitation (VR) services and to predict recovery. To incorporate SDT and SET as a framework for vocational recovery, developing and validating SDT/SET measures in vocational rehabilitation is warranted. Outcome expectancy is an important SDT/SET variable affecting rehabilitation engagement and recovery. Aims : The purpose of this study was to validate the Vocational Outcome Expectancy Scale (VOES) for use within the SDT/SET vocational recovery framework. Methods : One hundred and twenty-four individuals with serious mental illness (SMI) participated in this study. Measurement structure of the VOES was evaluated using exploratory factor analysis (EFA) and confirmatory factor analysis (CFA). Results : Both EFA and CFA results supported a two-factor structure: (a) positive outcome expectancy, and (b) negative outcome expectancy. The internal consistency reliability coefficients for both factors were acceptable. In addition, positive outcome expectancy correlated stronger than negative outcome expectancy with other SDT/SET constructs in the expected directions. Conclusions : The VOES is a brief, reliable and valid instrument for assessing vocational outcome expectancy in individuals with SMI that can be integrated into SDT/SET as a vocational rehabilitation engagement and recovery model in psychiatric rehabilitation.